2013
DOI: 10.1016/j.redox.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidoreductase-catalyzed reactive species generation: A process in critical need of reevaluation

Abstract: Nearly 30 years have passed since the discovery of xanthine oxidoreductase (XOR) as a critical source of reactive species in ischemia/reperfusion injury. Since then, numerous inflammatory disease processes have been associated with elevated XOR activity and allied reactive species formation solidifying the ideology that enhancement of XOR activity equates to negative clinical outcomes. However, recent evidence may shatter this paradigm by describing a nitrate/nitrite reductase capacity for XOR whereby XOR may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 49 publications
(19 reference statements)
1
152
0
5
Order By: Relevance
“…Its oxidase form is responsible for converting hypoxanthine to xanthine and xanthine to acid uric [33]. The purine cycle generates superoxide, hydrogen peroxide, and the reactive hydroxyl molecule [34], but uric acid itself is a potent non-enzymatic antioxidant [25]. Formed in the liver from hypoxanthine, it is released to the blood and either excreted or taken up by muscle, where it scavenges hydroxyl radical [35].…”
Section: Discussionmentioning
confidence: 99%
“…Its oxidase form is responsible for converting hypoxanthine to xanthine and xanthine to acid uric [33]. The purine cycle generates superoxide, hydrogen peroxide, and the reactive hydroxyl molecule [34], but uric acid itself is a potent non-enzymatic antioxidant [25]. Formed in the liver from hypoxanthine, it is released to the blood and either excreted or taken up by muscle, where it scavenges hydroxyl radical [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the required doses of allopurinol and oxypurinol are higher than the theoretical doses, and a pharmacological inhibitor may exert antioxidative effects [21]. In addition, studies have demonstrated that xanthine oxidase has several functions, including nitrate reductase activity, which increases production of nitric oxide [19, 20, 22]. The production of nitric oxide can minimize ischemia-reperfusion injury by stimulating vasodilation and inhibiting inflammatory responses.…”
Section: Mechanisms Of Xanthine Oxidase Induction Of Oxidative Stressmentioning
confidence: 99%
“…Not only transporters, but also transcriptional factors, signaling receptors, enzymes are involved in serum UA level. Table 1 shows association between life-style related diseases and UA metabolism [16][17][18][19][20][21][22][23][24] . Distinguishing cause and effect is difficult; some diseases raise SUA level, but UA affect disease onset or progression.…”
Section: Factors That Define Serum Uric Acid Levelsmentioning
confidence: 99%